Clinical analysis of high risk factors for pelvic malignant tumors after hysterectomy for benign diseases - Chao, Xiaopei (Medicine (Baltimore), 2019)
To analyze the clinicopathological characteristics of pelvic masses after hysterectomy for benign diseases, and to analyze the related factors of benign and malignant pelvic masses. This study retrospectively analyzed the patients undergone reoperation for pelvic mass subsequently to hysterectomy for benign disease from January 2012 to December 2016 in Peking Union Medical College Hospital. A total of 247 patients were enrolled in this study, of which 34.01% were diagnosed with malignant tumors, and 65.99% benign tumors. Comparing the clinicopathological data of patients with benign and malignant pelvic masses, significant differences were found between the 2 groups with regard to their ages of having hysterectomy and pelvic mass resection, and the time intervals between the onset of pelvic mass and hysterectomy. In addition, patients with malignant masses tended to complain of abdominal distension and abdominal pain, while most of those with benign masses were diagnosed during physical examination. Patients with malignant pelvic masses had medical imagines of mixed masses, extraovarian derivation, as well as elevated carbohydrate antigen-125 (CA 125). Multivariate analysis showed that ages of having hysterectomy, physical examination results, abnormal defecation, cystic and solid masses, and elevated CA 125 level were independent risk factors for benign and malignant pelvic masses. For patients having pelvic masses following hysterectomy for benign diseases, if they had hysterectomy later in their lives, and their masses were not found during physical examination, and had abnormal defecation, mixed cystic solid mass as well as elevated serum CA 125, it is suggested that special attention should be paid to the possibility of malignant tumors.